Catalyst-free synthesis of oxazol-2(3H)-ones from sulfilimines and diazo compounds through a tandem rearrangement/aziridination/ring-expansion reaction. Issue 13 (23rd April 2021) - Song, Lina; Tian, Xianhai; Han, Chunyu; Amanpur, Mehran; Rominger, Frank; Hashmi, A. Stephen K.
Abstract : Oxazol-2(3 H )-ones play a significant role in the fields of organic synthesis and drug development. Abstract : Oxazol-2(3 H )-ones play a significant role in the fields of organic synthesis and drug development. The classical synthesis of oxazol-2(3 H )-one derivatives requires high temperatures, metal catalysts, complex substrates or multi-step reactions. We report a concise synthesis of oxazol-2(3 H )-ones from readily available diazo compounds and sulfilimines through a tandem rearrangement/aziridination/ring-expansion reaction in the absence of any catalyst and additive. This reaction is scalable and the obtained products were readily converted to other valuable aza-heterocyclic frameworks.